2021
DOI: 10.1093/nutrit/nuab034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of herbs and spices on risk factors for cardiometabolic diseases: a review of human clinical trials

Abstract: Herbs and spices are recommended to increase flavor and displace salt in the diet. Accumulating evidence suggests herbs and spices may improve risk factors for cardiometabolic diseases. In this narrative review, an overview of evidence from human clinical trials examining the effect of herbs and spices on risk factors for cardiometabolic diseases is provided. Human clinical trials examining supplemental doses of individual spices and herbs, or the active compounds, have yielded some evidence showing improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 127 publications
0
8
0
Order By: Relevance
“…A randomized, controlled feeding study supported that adding a high dose (6.6 g • d −1 • 2100 kcal −1 ) of mixed culinary herbs and spices improves cardiometabolic health [3]. In addition, multiple single-herb/spice (turmeric, curcumin, cinnamon) feeding and supplementation studies have been conducted showing positive effects on lipid metabolism, glucose homeostasis, vascular health, and markers of inflammation and oxidative stress [48]. Nonetheless, data on the dietary intake of herbs and spices are limited.…”
Section: Dietary Interventions For Modulation Of Gut Microbiotamentioning
confidence: 96%
“…A randomized, controlled feeding study supported that adding a high dose (6.6 g • d −1 • 2100 kcal −1 ) of mixed culinary herbs and spices improves cardiometabolic health [3]. In addition, multiple single-herb/spice (turmeric, curcumin, cinnamon) feeding and supplementation studies have been conducted showing positive effects on lipid metabolism, glucose homeostasis, vascular health, and markers of inflammation and oxidative stress [48]. Nonetheless, data on the dietary intake of herbs and spices are limited.…”
Section: Dietary Interventions For Modulation Of Gut Microbiotamentioning
confidence: 96%
“…Moreover, the magnitude of ginger-associated changes varied among analyses, making the clinical meaningfulness of the outcomes unclear 10,85,86 . The interpretation of findings can be affected by different types and preparation methods of ginger supplements, method of daily administration, length of treatment, and the type and severity of disease 87 . One analysis concluded that population sample size and duration of intake were critical factors in influencing the effect of ginger on type 2 diabetes 57 .…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…10,85,86 The interpretation of findings can be affected by different types and preparation methods of ginger supplements, method of daily administration, length of treatment, and the type and severity of disease. 87 One analysis concluded that population sample size and duration of intake were critical factors in influencing the effect of ginger on type 2 diabetes. 57 Also, other factors that can confound outcomes were not consistently examined, such as gender, diet, exercise, smoking, and use of other relevant medications.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…The antioxidant properties of spices are largely known; besides their common use as food preservatives, spices display additional health benefits in the prevention and complementary treatment of oxidative stress-related disorders (e.g., cardiovascular diseases, neurodegenerative diseases, gastro-intestinal disorders, and cancers) [1,67]. Polyphenols and terpenoids are considered the main antioxidant compounds from spices that act as radical scavenging, reducing power, and metal chelating agents [3].…”
Section: Antioxidant Activity Of Extracts and Essential Oils Obtained...mentioning
confidence: 99%